Re-examining the reused Roman masonry at Rubers Law hillfort - Murphy, Kathryn; Crow, Jim; Gittings, Bruce (Proceedings of the Society of Antiquaries of Scotland, 2024)
Antiquarian exploration of the archaeological features on Rubers Law (NGR: NT 58030 15567), a large hill in the Scottish Borders, found approximately 30 worked Roman stones on the summit of the hill. Based on the prominent location and visibility from the site, these stones led to the conclusion that there had been a Roman tower on the hill, despite a lack of further supporting evidence. In order to investigate the possibility of a Roman structure on the hill, two surface surveys of the stone tumble were conducted in 2016 and 2017, locating almost 300 sandstone blocks around the summit of Rubers Law. The distribution of the stones was analysed using point density analysis in GIS and was examined in relation to the remaining archaeological features on the summit. Based on the hotspots in the distribution of the stones, the majority were in a tertiary context after being reused in the construction of a post-Roman nucleated hillfort. In light of recording a much larger number of Roman stones on Rubers Law, this paper also reinterprets the evidence for a Roman tower and explores other possible structures that could have been built on the summit.